Faktor yang Memengaruhi Pemanfaatan Pelayanan Kesehatan dalam Kegawatdaruratan Maternal Neonatal di Desa Bangun Rejo Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Marta Armita Silaban; Eva Dona Sinaga; Sari Simanjuntak; Sarah Sausan (Lembaga Pengembangan Kinerja Dosen, 2024)
Utilization of Emergency Maternal and Newborn Health Services is one of the important factors in determining the level of health which is particularly relevant to health problems and community development. The purpose of this study was to determine the factors that influence the utilization of health services in maternal and newborn emergencies in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province in 2024. This type of research is an analytical survey with a cross-sectional approach. Utilization of Health Services in maternal and newborn emergencies is the dependent variable in this study, while the independent variables include access to health services, attitudes of health workers and BPJS membership in Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency in 2024. The sampling technique was carried out using simple random sampling. The head of the family was the sample in this study. The sampling technique was carried out randomly from 476 Heads of Families in Bangun Rejo Village to 99 respondents. Data analysis used univariate and bivariate analysis with a confidence level of 95% (α = 0.05). The results of the chi-square test showed that there was a relationship between access to health services and the use of maternal neonatal emergency health services (p=0.04), there was no relationship between the attitude of health workers and the use of emergency health services (p=0.227), there was a relationship between BPJS membership and the use of maternal neonatal emergency health services (p=0.002).